Propuesta de una guia metodológica para la enseñanza de la tecnica de conducción de balón en niños de once – doce años de edad que inician la práctica de fútbol en el club “puebla junior” - Tanguila Tanguila, Cristian Edwin (2016)
In the present investigation due to the evolution it has had, in recent times, it has tried to reach the greatest achievements in the sports field and for this the formative divisions have been created, this is done in order to take new figures In the sports field, for this reason we have proposed a methodological guide for the teaching of the technique of conducting the ball in children of eleven - twelve years of age who begin the practice of football in the club "junior puebla", the general objective Was: Design a methodological guide for the teaching of the technique of conduction of the ball in children of eleven - twelve years. During this process different methods and techniques were considered, including the scientific method, inductive-deductive, analytical-synthetic, descriptive, techniques, such as the survey and applied to the 4 coaches 60 students. With all the information arsenal of the application of the instruments it was possible to obtain positive results improving the processes of teaching learning and with it to execute properly the fundamentals technique of conduction of ball in the 100% of the children with this it can be evidenced that they are in Process of mastering the fundamentals, and in conclusion the study made it possible to characterize the debentrenamiento sportive process, which made possible the determination of a set of components so that the children can be better developed in the sport and as a recommendation to execute a program teaching fundamentals Soccer coaches designed pedagogically taking into account the characteristics of the stage of sports initiation.